Ephemeral art in impermanent spaces: the effects of street art in the social construction of public space - Sequeira, A. D. (2019)
This article sets out to show how the production and practices of street art in Lisbon have strong effects on what concerns the creation of images of the city – in its marketable consequences – and the promotion of discourses about the urban public space and its structures. Because street art displays a very particular relation with the urban space, the research on the dynamics that its practice and production create with the actors and institutions that shape the cities, show that it has an active role in creating images of the city, as well as proposing discourses about its public space. This article results from a research on street art and its implications in the social construction of public space, from the urban context of Lisbon. Within this research, street art is conceived as an art world in formation, specific as it exists in-between an underground practice and a full participation in the contemporary art world and its markets.